10 kHz Spinal Cord Stimulation for Treatment of Painful Diabetic Neuropathy - A Multicenter Randomized Controlled Trial. (16th November 2020) - Petersen, Erika A; Stauss, Thomas; Scowcroft, James; White, Judith; Sills, Shawn; Amirdelfa, Kasra; Guirguis, Maged; Xu, Jijun; Yu, Cong; Nairizi, Ali; Patterson, Denis; Galan, Vincent; et al.
Abstract: INTRODUCTION: Approximately 6 million adults in the US are living with painful diabetic neuropathy (PDN). 1, 2 Neither pharmacological treatments nor low-frequency spinal cord stimulation (SCS) provides long-term relief; 3-6 however, preliminary data suggest 10 kHz SCS relieves pain and improves sensory deficits from peripheral polyneuropathy.7 METHODS: In total, 216 subjects were assigned 1:1 to 10 kHz SCS (Nevro Corp.) combined with conventional medical management (CMM) or CMM alone. Key inclusion criteria: diagnosis of PDN with symptoms ≥12 months, lower limb pain intensity ≥5 cm (on a 0–10 cm visual analog scale [VAS]), and appropriate candidate for SCS. Key exclusion criteria: hemoglobin A1c >10%, daily opioid dosage >120 mg morphine equivalents, and upper limb pain intensity ≥3 cm. Outcomes include pain, neurological function, sleep quality, patient satisfaction, and cost-effectiveness. Follow-up will last 24 months. RESULTS: Randomization allocated 113 subjects to 10 kHz SCS+CMM and 103 to CMM treatment arms that were well-matched for baseline characteristics. There were no reported study-related adverse events for CMM group and 19 reported in 10 kHz SCS+CMM group up to 3 months. There were 2 procedure-related infections in the 10 kHz SCS+CMM group (1.8%). Per-protocol analysis revealed 5% of CMM and 86% of 10 kHz SCS+CMM subjects met the primary endpoint ( P < 0.001). At 3-month follow-up, there were differences in lower limb pain scores, responder rates, and Investigator-assessed sensory improvements. In addition, differences between treatment groups were observed across several HRQoL measures, such as sleep and global impression of change as rated by patient and clinician. CONCLUSION: SENZA-PDN is the largest RCT to-date of SCS management of PDN and will inform the treatment continuum. Primary endpoint met with significant proportion of subjects responding to 10 kHz SCS.